Authenticity and presence: defining perceived quality in VR experiences - Hameed, Asim; Perkis, Andrew (Frontiers in Psychology, 2024)
This work expands the existing understanding of quality assessments of VR experiences. Historically, VR quality has focused on presence and immersion, but current discourse emphasizes plausibility and believability as critical for lifelike, credible VR. However, the two concepts are often conflated, leading to confusion. This paper proposes viewing them as subsets of authenticity and presents a structured hierarchy delineating their differences and connections. Additionally, coherence and congruence are presented as complementary quality functions that integrate internal and external logic. The paper considers quality formation in the experience of authenticity inside VR emphasizing that distinguishing authenticity in terms of precise quality features are essential for accurate assessments. Evaluating quality requires a holistic approach across perceptual, cognitive, and emotional factors. This model provides theoretical grounding for assessing the quality of VR experiences.